3(x-3)=2-8x

Simple and best practice solution for 3(x-3)=2-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)=2-8x equation:


Simplifying
3(x + -3) = 2 + -8x

Reorder the terms:
3(-3 + x) = 2 + -8x
(-3 * 3 + x * 3) = 2 + -8x
(-9 + 3x) = 2 + -8x

Solving
-9 + 3x = 2 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-9 + 3x + 8x = 2 + -8x + 8x

Combine like terms: 3x + 8x = 11x
-9 + 11x = 2 + -8x + 8x

Combine like terms: -8x + 8x = 0
-9 + 11x = 2 + 0
-9 + 11x = 2

Add '9' to each side of the equation.
-9 + 9 + 11x = 2 + 9

Combine like terms: -9 + 9 = 0
0 + 11x = 2 + 9
11x = 2 + 9

Combine like terms: 2 + 9 = 11
11x = 11

Divide each side by '11'.
x = 1

Simplifying
x = 1

See similar equations:

| x-3=.75(2-x)+6 | | 2h-3h=15 | | X/0.4=11.25 | | 11x^2=44x | | 5x/x=(8x^3)/x^2 | | Y-4=-8.4 | | lnx^2+3x-1=0 | | -(-2n-5)=-13-n | | 2(3*-4)=22 | | x11/20*30 | | x=11/30x230 | | 4k-5=6k+1 | | 5(m-4)=2m+3 | | -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 | | 17x-6=10x-13 | | p=2x+58 |

Equations solver categories